Zacharias representation of effective associative rings. (July 2020) - Mora, Teo
Abstract: The techniques introduced by Szekeres and Zacharias in order to extend Buchberger Theory from polynomials over a field to polynomials over a Noetherian domain are here generalized to monoid rings.